Chronic inflammatory demyelinating polyneuropathy-like neuropathy as an initial presentation of Crohn’s disease - Kim, Suji (BMC Neurol, 2015)
BACKGROUND: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare complication of Crohn's disease (CD), and it is uncertain whether it is associated with CD itself or with its treatment. We describe a case of CIDP-like neuropathy as an initial symptom of CD. The neurologic symptoms of the patient which responded partially to intravenous immunoglobulin (IVIG) recovered after resection of the appendiceal CD. CASE PRESENTATION: A 17-year-old male had experienced three separate attacks of motor weakness and paresthesia of all four extremities over a period of 7 months. The electrophysiologic findings revealed a demyelinating sensory-motor polyneuropathy which was compatible with CIDP. However, repeated intravenous IVIG (2 g/kg) treatment gave only a partial response. Four days after the last discharge, he was diagnosed as appendiceal CD after surgical resection of a periappendiceal abscess. His neurologic symptoms and electrophysiologic findings recovered without any maintenance therapy. CONCLUSIONS: CIDP-like neuropathy can be an initial presentation of CD, and recovery of the CIDP symptoms may result from resection of the CD. Clinicians should be aware of the possibility of CD in patients with intractable CIDP symptoms.